New Immigrants in Local Food Systems: Two Iowa Cases - L. Flora, Jan; Emery, Mary; Thompson, Diego; M. Prado-Meza, Claudia; B. Flora, Cornelia (The International Journal of Sociology of Agriculture and Food, 2012)
Integrating immigrants in local food systems involves negotiations between complex meaning systems. An experience in working with immigrants and local food efforts in two Iowa communities shows that new social relationships are intersected by critical aspects such as trust (a component of social capital), political power (political capital), knowledge (human capital), and ethnic and cultural world views (cultural capital). Our analysis identified subtle and unrecognized hegemonic behavior and racialization (an unacknowledged culture of whiteness within the local/alternative food system) that inadvertently excludes Latinos and immigrants from the local food system. For these Latino farmers and gardeners, sharing agricultural produce with family and friends was more import than market-oriented strategies. Food is a major transmitter of cultural capital and builds social capital with extended family and with others in the community. By substituting food produced by the family for purchased food, family and friends receive a better diet and perhaps lower food costs. Growing and preparing food offers a way to give back to the community. Participation in farmer training fostered an inclusive, diverse and participatory community, but that did not extend to effective inclusion of Latino residents in the local food group nor to an effective inter-cultural incubator farm. It may be that a farm incubator with a focus on immigrant farmers would be more successful if it were not directly linked to an educational institution. The outside organizers inadvertently strengthened a culture of whiteness, as they had different goals for the food system than did the local participants.